2015
DOI: 10.1371/journal.pone.0141417
|View full text |Cite
|
Sign up to set email alerts
|

Language and Memory Improvements following tDCS of Left Lateral Prefrontal Cortex

Abstract: Recent research demonstrates that performance on executive-control measures can be enhanced through brain stimulation of lateral prefrontal regions. Separate psycholinguistic work emphasizes the importance of left lateral prefrontal cortex executive-control resources during sentence processing, especially when readers must override early, incorrect interpretations when faced with temporary ambiguity. Using transcranial direct current stimulation, we tested whether stimulation of left lateral prefrontal cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 144 publications
(162 reference statements)
6
47
1
Order By: Relevance
“…It is known that after stroke may occur a change in synaptic homeostasis, which affects individuals' cognition (21) . In the present study the verbal and visual WM showed significant improvements after the use of tDCS, supporting the results found in diverse population by other authors (22,23) . One possible explanation is that the modulation of membrane action potencial induced by tDCS could limit this homeostasis lost, therefore mantaining the cognitive functions (24) .…”
Section: Discussionsupporting
confidence: 93%
“…It is known that after stroke may occur a change in synaptic homeostasis, which affects individuals' cognition (21) . In the present study the verbal and visual WM showed significant improvements after the use of tDCS, supporting the results found in diverse population by other authors (22,23) . One possible explanation is that the modulation of membrane action potencial induced by tDCS could limit this homeostasis lost, therefore mantaining the cognitive functions (24) .…”
Section: Discussionsupporting
confidence: 93%
“…And, as sketched earlier, neuroimaging findings show co-localization of activity within the LIFG when the same subjects perform a canonical cognitive control task (Stroop, Flanker) and a sentence-processing task involving syntactic conflict (January et al, 2009; van de Meerendonk et al, 2013; Ye & Zhou, 2009). These correlational findings have been bolstered by recent work demonstrating a causal connection between cognitive control procedures and language processing: extensive practice on a cognitive control tasks leads to improved garden-path recovery (Hussey et al, 2016; Novick, Hussey, Teubner-Rhodes, Harbison, & Bunting, 2014); transcranial direct current stimulation of VLPFC mitigates the effects of syntactic ambiguity during real-time processing (Hussey, Ward, Christianson, & Kramer, 2015); and dynamic cognitive control engagement immediately facilitates recovery from misinterpretation during online comprehension (Hsu & Novick, 2016). …”
Section: Introductionmentioning
confidence: 94%
“…Adjudication between the resulting semantic representations, including full inhibition of one of the representations if required by the task at hand, requires time and effort (cf. Hussey et al, 2015)."Good-enough" processing is usually quite effective and accurate in normal linguistic environments; however, when materials are constructed to contain temporary ambiguities or to pit structure and semantics against one another (as is the case here), comprehension errors are frequently observed. Importantly for the present study, previous results within the good-enough framework predict the following interaction of structural difficulty and plausibility.…”
mentioning
confidence: 90%
“…Evidence suggests that misinterpretations are derived from competition between the syntactic structure of the verbatim input and other information sources, i.e., various processing heuristics that can, under certain circumstances, overwhelm the syntactic structure (e.g., Christianson et al, 2001Christianson et al, , 2010Christianson & Luke, 2011;Christianson, Williams, Zacks, & Ferreira, 2006;Ferreira, 2003;den Ouden, Dickey, Anderson, & Christianson, 2016;Ferreira, Bailey, & Ferraro, 2002;Hussey, Ward, Christianson, & Kramer, 2015).…”
Section: Good-enough (Ge) Processing Theorymentioning
confidence: 99%
See 1 more Smart Citation